Visualization of Ceramide-Associated Proteins in Ceramide-Rich Platforms Using a Cross-Linkable Ceramide Analog and Proximity Ligation Assays With Anti-ceramide Antibody - Jiang, Xue; Zhu, Zhihui; Qin, Haiyan; Tripathi, Priyanka; Zhong, Liansheng; Elsherbini, Ahmed; Karki, Sanjib; Crivelli, Simone M.; Zhi, Wenbo; Wang, Guanghu; Spassieva, Stefanka D.; Bieberich, Erhard (Frontiers in Cell and Developmental Biology, 2019)
Ceramide-rich platforms (CRPs) mediate association of proteins with the sphingolipid ceramide and may regulate protein interaction in membrane contact sites to the cytoskeleton, organelles, and infectious pathogens. However, visualization of ceramide association to proteins is one of the greatest challenges in understanding the function of ceramide. Here we introduce a novel labeling technique for ceramide-associated proteins (CAPs) by combining photoactivated cross-linking of a bioorthogonal and bifunctional ceramide analog, pacFACer with proximity ligation assays (PLAs). PLAs use antibodies to: 1) the candidate CAP and the fluorophore covalently attached to pacFACer that is cross-linked to the CAP (PLA1); or 2) the CAP and ceramide (PLA2). PLA1 shows the subcellular localization of a particular CAP that is cross-linked to pacFACer, while PLA2 tests if the cross-linked CAP forms a complex with endogenous ceramide. Two proteins, tubulin and voltage-dependent anion channel 1 (VDAC1), were cross-linked to pacFACer and showed PLA signals for a complex with ceramide and pacFACer, which were predominantly colocalized with microtubules and mitochondria, respectively. Binding of tubulin and VDAC1 to ceramide was confirmed by coimmunoprecipitation assays using anti ceramide antibody. Cross-linking to pacFACer was confirmed using click chemistry-mediated attachment of biotin and streptavidin pull-down assays. Inhibition of ceramide synthases with fumonisin B1 (FB1) reduced the degree of pacFACer cross-linking and complex formation with ceramide, while it was enhanced by amyloid beta peptide (Aβ). Our results show that ceramide is critical for mediating cross-linking to pacFACer and that a combination of cross-linking with PLAs (cross-link/PLA) for ceramide is a novel tool to visualize CAPs and to understand the regulation of protein interaction in CRPs.